-5x-3(-2x-18)=62

Simple and best practice solution for -5x-3(-2x-18)=62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-3(-2x-18)=62 equation:


-5x -3(-2x - 18) = 62

We simplify the equation to the form, which is simple to understand
-5x-3(-2x-18)=62

Reorder the terms in parentheses
-5x+(+6x+54)=62

Remove unnecessary parentheses
-5x+6x+54=+62

We move all terms containing x to the left and all other terms to the right.
-5x+6x=+62-54

We simplify left and right side of the equation.
+1x=+8

We divide both sides of the equation by 1 to get x.
x=8

See similar equations:

| 6r-21=3(3+7r) | | 3x+25-14=7x+4-5x | | 2t+3t=21 | | y=2x-21 | | x^2-xy-56y^2= | | x=-2y-14 | | 3x^2+243= | | (0.3x-3x)+0.8=0.6 | | 2(3t)+(2t)=21 | | 6x-5=85 | | y=-4x+27 | | 16y^2-25=0 | | -5(4b+1)+(21b-1)=0 | | .18x=2(3x+6) | | 0.3x-3x+0.8=0.6 | | 3(v+5)=12 | | 4=-5p+4p | | y^7-16y^3= | | 9z-6z=10+3+2 | | 15x-7x=52-5x | | 7+2n-5=5n+9-2n | | m/8-7=12 | | -2y+8=-4 | | 8x-4=84 | | y^6-256y^2= | | 29+2x=159 | | 2+5x+6=-7 | | 25y^2+15y+2= | | c/2+3=15 | | 2=0.8*x | | -12x+76=3x+4 | | 5(2t-2)=35 |

Equations solver categories